MESIN PRESS PAVING BLOCK MENGGUNAKAN ELECTRIC JACK KAPASITAS 2 TON BERBAHAN DASAR SAMPAH PLASTIK - Ramadhan, Yanuar (Nozzle : Journal Mechanical Engineering, 2023)
Abstract  The paving block press machine uses a 2 ton capacity electric jack made from plastic waste which functions to press and melt, with the help of an electric jack. The aim of this research is to determine the process of making an electric jack press machine with a capacity of 2 tons from plastic waste. In this research, the method used is a descriptive qualitative method, because the research will only explain how the process and manufacture of an electric jack press machine with a capacity of 2 tons is made from plastic waste. Therefore, research activities are only limited to finding out about the tools and materials needed in the process of making the machine using the cutting process, welding process, sanding process, assembly process, painting process.